Chemical Characterization and Cytotoxic/Antibacterial Effects of Nine Iranian Propolis Extracts on Human Fibroblast Cells and Oral Bacteria. (6th April 2022) - Yazdanian, Mohsen; Motallaei, Mohammad Nima; Tahmasebi, Elahe; Tebyaniyan, Hamid; Alam, Mostafa; Abbasi, Kamyar; Seifalian, Alexander; Ranjbar, Reza; Yazdanian, Alireza; Hosseini, Hamideh Mahmoodzadeh; Moghaddam, Mehrdad Moosazadeh
Abstract : Multimicrobial infections caused by pathobionts are called dysbiotic multimicrobial illnesses. Commercial mouthwashes, such as chlorhexidine, have negative side effects that can prevent tooth decay and infection. The present study aimed to determine the antifungal, antibacterial, and cytotoxicity characteristics of the propolis extracts from different areas (Iran). The ethanolic extract of propolis was prepared. GC/MS carried out the characterization to determine the thymol, carvacrol, and menthol extracts, and also, total phenol and flavonoid were assed for all samples. The antimicrobial and antibiofilm effects were evaluated against S. mutans, S. mitis, S. salivarius, L. acidophilus, E. coli, S. aureus, and C. albicans. The cytotoxic effect of extracts was measured on human fibroblast cells by MTT test. The MIC values in mg mL -1 were ranged as follows: S. salivarius (0.003 to 0.048), S. mutans (0.003 to 0.029), S. mitis (0.007 to 0.058), L. acidophilus (0.007 to 0.117), C. albicans (0.014 to 0.234), E. coli (0.007 to 0.058), and S. aureus (0.007 to 0.058), while MBC were, respectively, S. mutans (0.007 to 0.058), S. salivarius (0.007 to 0.117), S. mitis (0.007 to 0.117), L. acidophilus (0.014 to 0.234), C. albicans (0.029 to 0.468), E. coli (0.014 to 0.234), and S. aureus (0.007 to 0.117). Cariogenic bacteria and Candida albicans were demonstrated to be resistant to propolis extracts. Therefore, propolis extracts may make good mouthwashes.